Enrique Pichon-Rivière: origins of Argentinian social psychology - Becerra, Gastón (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2015)
Enrique Pichon-Rivière (1907-1977) was one of the founders of social psychology in Argentina. Here we review his biography and institutional paths along with his theoretical and epistemological contributions. We argue that Enrique Pichon-Rivière evinced a critical attitude towards the disciplinary divisions, and the distance between academic knowledge and social praxis. Here we prioritize those aspects of his work that we consider most relevant to the social sciences, including their notions of social needs, learning matrix, conceptual, referential, and operational schema (E.C.R.O., for his Spanish acronyms) and convergent epistemology